Macromolecular protein complexes : structure and function - Harris, J. Robin; Marles-Wright, Jon (Springer, 2017)
This volume of the established Subcellular Biochemistry series presents 20 chapters dealing with a broad range of interesting protein complexes. It will enable researchers to readily appreciate the major contribution from both X-ray crystallography and cryo-electron microscopy in this field of study. The biological significance of these structural studies is emphasised throughout the book. The diversity of the material included here indicates the breadth of this field and the tremendous progress that has been made in recent years. The book is directed primarily to advanced students and researchers in structural biology, and others in the biochemical sciences. It will be supplemented by other related books within the Subcellular Biochemistry series. One of the Editors (JM-W) is actively involved in structural biology and the other (JRH), as a retired academic and the Series Editor of Subcellular Biochemistry, has long experience at editing multi-author books.- Resumé vydavatel
Keywords: strukturní biologie; biochemie; bílkoviny; structural biology; biochemistry; proteins; elektronické knihy; sborníky; electronic books; papers of several authors